Defending plurality : : four reasons why we need to rethink academic freedom in Europe - Schubert, Karsten (2021)
Abstract: Academic freedom is under attack, both in authoritarian democracies, such as Hungary and Turkey, and in liberal Western democracies, such as the United States, the UK, France and Germany. For example, Gender Studies are being targeted by right-wing governments in Eastern Europe, and in France President Emmanuel Macron has attacked post-colonial and critical theories as “Islamo-gauchisme“, portraying them as a danger to the Republic. However, dominant discourses about academic freedom and free speech in the global north, lately especially in France and Germany, focus on an alleged threat to academic freedom through “political correctness” and “cancel culture”, that, under scrutiny, often turn out to be exactly the opposite, namely defences of plurality and critical voices